Studying the Role of Positive Reinforcement for Motivation to Learn the English Language at Secondary Level in Pakistan - Muhammad Safdar Bhatti; Asif Iqbal; Rafia Mukhtar; Shaista Noreen; Zahida Javed (Utamax : Journal of Ultimate Research and Trends in Education, 2021)
English is being used all over the world as an international language. It is a Lingua Franca that enjoys a supreme status in society. Learners have to wrestle with new vocabulary, rules of grammar, pronunciation, and more. So, the current study explores the students’ motivation and the perceptions of English teachers about positive reinforcement in an English language classroom. Motivation and attitudes in learning a language in the classroom are very important and may make language courses more stimulating. The study contained a quantitative paradigm of control and experimental group as the research design. One hundred students and thirty teachers were selected using a simple random sampling technique. The data were collected using a close-ended self-developed questionnaire of 30 items with five main indicators subdivided into six indicators. The collected data was analysed in SPSS. The results demonstrated that Pakistani students were motivated in learning the English language and have shown a positive attitude towards using reinforcement in the classrooms. The study also spotlighted that if the motivation is used efficiently in the classroom, it will be a high-ranking tool for language learning. The recommendations and findings of this study should be taken into careful consideration, and steps should be taken to implement them in Pakistani English language classrooms.